The Role of Traditional Media in India's Digital Advertising Landscape: Coexistence or Decline? - Sivanandan, Chithra (Journal of Global Economy, Business and Finance, 2025)
With the rapid growth of digital advertising, the role of traditional media such as television, radio, and print in India has come under scrutiny. This paper explores whether traditional media is in decline or whether it continues to coexist with its digital counterparts. Despite the rise of online platforms and digital marketing, traditional media still holds significant value, particularly in regional markets and among older demographics. This paper examines the coexistence of traditional and digital advertising, analyzing shifts in consumer behavior, the importance of media diversity in a country as vast as India, and the potential for traditional media to evolve through integration with digital tools. The paper concludes with insights into how brands can effectively balance traditional and digital channels to reach India's diverse audience.